(untitled) - Frenzel, Louis E. (Boston, [Mass.], 2008)
Developed by well-known electronics author Louis Frenzel, Principles of Electronic Communication Systems offers the most up-to-date coverage of the rapidly changing communications field. Appropriate for use in a one- or two-semester course, this text offers everything needed to prepare students to work in the increasingly complex communications industry of the 21st century.
Keywords: Electronic systems,Digital communications,Hệ thống điện tử,Thông tin số